The plasma cell associated antigen detectable by antibody VS38 is the p63 rough endoplasmic reticulum protein. Issue 6 (June 1997) - Banham, A H; Turley, H; Pulford, K; Gatter, K; Mason, D Y
Abstract : AIMS: To characterise the 64 kDa intracellular antigen present on normal and neoplastic plasma cells detected by monoclonal antibody VS38 and by another antibody, MC186, of similar reactivity. METHODS: The VS38 monoclonal antibody was used to screen a bacterially expressed peripheral blood cDNA library, and the immunocytochemical staining of the two antibodies was compared with those raised specifically to the protein identified as the VS38 antigen. RESULTS: A partial cDNA encoding the VS38 antigen was cloned and shown to be identical to the human p63 gene. p63 is a non-glycated, reversibly palmitoylated type II transmembrane protein which is found in rough endoplasmic reticulum. Antibody MC186 also recognised this protein and both VS38 and MC186 together with two antibodies raised to p63 gave identical immunostaining patterns. CONCLUSIONS: The VS38 antigen was identified as the rough endoplasmic reticulum protein p63. While it is not exclusively expressed on plasma cells, the presence of p63 distinguishes plasma cells from other lymphoid cells because of their high secretory activity.